(untitled) (Applied Biological Research, 2025)
The study was carried out to formulate and evaluate the suitability of different germinated millet flour incorporation in mango, pineapple and pomegranate ready-to-serve (RTS) beverages. Incorporation of germinated foxtail millet or little millet flour @ 1% in mango, pineapple and pomegranate RTS beverages showed high dialyzable iron in germinated foxtail millet incorporated (GFMI) mango (2.47 µg mL-1), GFMI pineapple (2.68 µg mL-1) and GMFI pomegranate (1.65 µg mL-1) RTS beverages as compared to the germinated little millet incorporated (GLMI) mango (1.51 µg mL-1), GLMI pineapple (1.11 µg mL-1) and GLMI pomegranate (1.38 µg mL-1) RTS beverages and respective control samples. Similarly, predicted glycemic index (GI) was 95.76 to 105.91, 93.86 to 103.90 and 98.62 to 110.60 in germinated foxtail millet flour, little millet flour incorporated beverages and their control samples, respectively; even though the GI of all the samples did not fall under low GI range. The findings suggest that germinated millet flours can be incorporated to increase dialyzable iron content and reduce GI of fruit beverages with further increasing the incorporation amount in fruit beverages and validation with adequate in vivo studies.